SCMA codebooks design for Rayleigh fading channel - Tuofeng LEI; Shuyan NI; Naiping CHENG; Xin SONG (Tongxin xuebao)
According to the symbol error eate (SER) of the superimposed constellation, the near-optimal space code multiple access (SCMA) codebooks were explored under uplink and downlink Rayleigh fading channels, respectively.A near-optimal codebook design scheme was proposed based on the mathematical model between the superimposed constellation and the SER formula.And the proposed design procedures could be summarized as follows, design the factor graph matrix, match the best codeword pair, and find the optimal angle.Numerical results are provided to demonstrate that the proposed scheme can achieve near-optimal SER performance.